Agricultural policies in Indonesia: producer support estimates 1985-2002 - Thomas, Marcelle; Orden, David (International Food Policy Research Institute, 2004)
As in many other developing countries, the concerns about food security in Indonesia during the 1980s and early 1990s resulted in policies aimed at achieving self-sufficiency in food crops. The Government of Indonesia (GOI) combined price interventions and economic incentives to encourage agricultural production, especially of the staple crops. From 1985 to 1998, Indonesia started a series of domestic and trade reforms emanating from a combination of unilateral undertakings, the country’s commitments to the WTO, and the government’s agreement with the IMF following the 1997/98 financial crisis. This study computes nominal protection rates and producer support estimates (NPR and PSE) for Indonesia for the period 1985-2003 for six agricultural commodities, rice, maize, sugar, soybeans, crude palm oil, and natural rubber (representing more than two-thirds of Indonesian agricultural output) in an attempt to quantify the net effects of these policies. The NPRs and PSEs computed for Indonesia show that in spite of the reforms, the GOI has protected its agriculture over the past twenty years, although not uniformly across commodities. Although the reforms went a long way in reducing trade and domestic regulations on agricultural products, the study results demonstrate a return to protection for some commodities in recent years.